Complementarity and Financial Systems - A. Hackethal; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1999)
Individual financial systems can be understood as very specific configurations of certain key elements. Often these configurations remain unchanged for decades. We hypothesize that there is a specific relationship between key elements, namely that of complementarity. Thus, complementarity seems to be an essential feature of financial systems. Intuitively speaking, complementarity exists if the elements of a (financial) system reinforce each other in terms of contributing to the functioning of the system. It is the purpose of this paper to provide an analytical clarification of the concept of complementarity. This is done by modeling financial systems as combinations of four elements: firm-specific human capital of an entrepreneur, the ability of a bank to restructure the borrower's firm in the case of distress, the possibility to appropriate private benefits from running the firm, and the bankruptcy law. A specific configuration of these elements constitutes one financial system. The bankruptcy law and the potential private benefits are treated as exogenous. They determine the bargaining power of the contracting parties in the case that recontracting occurs. In a two-stage game, the optimal values for the other elements are determined by the agents individually - by investing in human capital and restructuring skills, respectively - and jointly by writing, executing and possibly renegotiating a financing contract for the firm. The paper discusses the equilibria for different types of bankruptcy law and demonstrates that equilibria exhibit the sought-after feature of complementarity. Three particularly significant equilibria correspond to stylized accounts of the British, German and the US-American financial system, respectively.
urn:nbn:de:hebis:30-18176
Keywords: G20; G21; G30; G33; 330; Bankruptcy Law; Banks; Complementarity; Financial Systems; Finanzsektor; Finanzsystem; Insolvenz; Unternehmensfinanzierung; Bank; Spieltheorie; Prinzipal-Agent-Theorie; Theorie